Vibration reduction in a tilting rotor using centrifugal pendulum vibration absorbers. (22nd December 2016) - Shi, Chengzhi; Shaw, Steven W.; Parker, Robert G.
Abstract: This paper investigates vibration reduction in a rigid rotor with tilting, rotational, and translational motions using centrifugal pendulum vibration absorbers (CPVAs). A linearized vibration model is derived for the system consisting of the rotor and multiple sets of absorbers tuned to different orders. Each group of absorbers lies in a given plane perpendicular to the rotor rotation axis. Gyroscopic system modal analysis is applied to derive the steady-state response of the absorbers and the rotor to external, rotor-order, periodic forces and torques with frequency m Ω, where Ω is the mean rotor speed and m is the engine order (rotor-order). It is found that an absorber group with tuning order m is effective at reducing the rotor translational, tilting, and rotational vibrations, provided certain conditions are met. When the periodic force and torque are caused by N substructures that are equally spaced around the rotor, the rotor translational and tilting vibrations at order j are addressed by two absorber groups with tuning orders jN ±1. In this case, the rotor rotational vibration at order j can be attenuated by an absorber group with tuning order jN . The results show how the response depends on the load amplitudes and order, the rotor speed, and design parameters associated with the sets of absorbers, most importantly, their tuning, mass, and plane of placement. In the ideal case with zero damping and exact tuning of the absorber sets, the vibrations can be eliminated for a range of loads over which the linearized model holds. The response for systems with detuned absorbers is also determined, which is relevant to applications where small detuning is employed due to robustness issues, and to allow for a larger range of operating loads over which the absorbers are effective. The system also exhibits undesirable resonances very close to these tuning conditions, an issue that is difficult to resolve and deserves further investigation.